2019
DOI: 10.1002/adsc.201901047
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Cycloalkene‐1‐carboxamides with Aryl Boronates via Rhodium(III)‐Catalyzed C−H Activation: A Versatile Route to 3,4‐Cycloalkaquinolin‐2(1H)‐ones

Abstract: Under rhodium(III) catalysis, substituted N‐methoxycycloalkene‐1‐carboxamides successfully reacted with aryl boronic acid pinacol esters to provide 3,4‐cycloalkaquinolin‐2(1H)‐ones via direct functionalization of the β‐alkenyl C−H bond and form C−C/C−N bond in one pot. The gram‐scale synthesis of the title compound demonstrated the great synthetic utility of this methodology.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The Zhu group was able to construct the same scaffolds through an efficient Cp*Rh(III)-catalyzed alkenyl C−H functionalization of N-methoxycycloalkene carboxamides with aryl boronic acid pinacol esters (Scheme 204). 347 Even though asymmetric C−H activation is extremely useful for obtaining chiral compounds, controlling their stereochemistry is an extremely difficult task in some cases. 348−352 Enantioselective C−H functionalization often demands harsh reaction conditions and high temperature that are incompatible with many asymmetric reactions.…”
Section: 37mentioning
confidence: 99%
See 1 more Smart Citation
“…The Zhu group was able to construct the same scaffolds through an efficient Cp*Rh(III)-catalyzed alkenyl C−H functionalization of N-methoxycycloalkene carboxamides with aryl boronic acid pinacol esters (Scheme 204). 347 Even though asymmetric C−H activation is extremely useful for obtaining chiral compounds, controlling their stereochemistry is an extremely difficult task in some cases. 348−352 Enantioselective C−H functionalization often demands harsh reaction conditions and high temperature that are incompatible with many asymmetric reactions.…”
Section: 37mentioning
confidence: 99%
“…The Zhu group was able to construct the same scaffolds through an efficient Cp*Rh­(III)-catalyzed alkenyl C–H functionalization of N -methoxycycloalkene carboxamides with aryl boronic acid pinacol esters (Scheme ). A variety of N -methoxycycloalkene carboxamide derivatives reacted smoothly with diverse aryl boronates in the presence of 5 mol % [RhCp*Cl 2 ] 2 catalyst and 2 equiv of Ag 2 O oxidant to furnish the corresponding cycloalkaquinolinones in up to 92% yield. On the basis of detailed mechanistic investigations, the authors revealed that this annulative transformation may occur via a dual C–H activation pathway.…”
Section: Alkenyl C–h Bond Functionalization Of Alkenes Containing An ...mentioning
confidence: 99%
“…In 2019, Zhu reported a Rh-catalyzed, amide-directed, double C–H bond activation strategy to prepare cycloalkaquinolones 66 with arylboronic acid 64 pinacol esters 65 ( Scheme 18 ) [ 102 ]. The products were obtained in moderate to excellent yields and showed broad scope and high functional group tolerance.…”
Section: Two-component Reactionsmentioning
confidence: 99%